2005
DOI: 10.1007/bf03021781
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic Anesthesia, Respiration and Airway

Abstract: Low-dose ITM for cardiac surgery did not delay early extubation, but it improved postoperative analgesia and pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies have analyzed the effect of ITMA on postoperative lung function. In 2 randomized controlled trials, ITMA was associated with an improved forced vital capacity (FVC) and forced expiratory volume (FEV) after cardiac surgery [ 26 , 27 ]. In contrast, dos Santos et al found a similar decline of the FVC and FEV in patients with ITMA and IVA that was likely attributed to the high intravenous opiate doses that were given in both groups [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analyzed the effect of ITMA on postoperative lung function. In 2 randomized controlled trials, ITMA was associated with an improved forced vital capacity (FVC) and forced expiratory volume (FEV) after cardiac surgery [ 26 , 27 ]. In contrast, dos Santos et al found a similar decline of the FVC and FEV in patients with ITMA and IVA that was likely attributed to the high intravenous opiate doses that were given in both groups [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that intraoperative stress responses in CABG patients were decreased with HSA, with these individuals also exhibiting enhanced preservation of beta-receptor function [ 16 ]. HSA may also improve aspects of post-operative pain management in patients following either cardiac or non-cardiac surgery [ 17 – 19 ]. We that note a comprehensive meta-analysis of clinical outcome data, specifically focussed on mortality and cardiovascular morbidity, did not indicate benefits from incorporation of spinal analgesia [ 20 ].…”
Section: Introductionmentioning
confidence: 99%